Silenced By Design and Displaced By Will: A Foucauldian Study of Native American Literature - Aqdas, Khanam (2023)
The study seeks to explore how in the pertaining hegemonic scenario of the White world the Native American literature offers a critical perception on some of the vital present day issues of survival, resilience and power imbalance that they are facing. The selection of literary works is made from a range of genres written by different Native Americanwriters over the last four decades. Undertaken dissertation debates that the Native American literature addresses the issues that are disrupting the indigenous culture. It encounters the false formation of the Native Americans as misnomers through the dominant White narratives. The works of Sherman Alexie, Thomas King, Doug Boyd and Louise Erdrich selected for analysis incorporate the complex aspects of the Native American literature, culture and history in the milieu of the subjective perspectives and experiences of the writers. By incorporating close reading method as the methodological approach, this study has attempted to read across Native American texts by applying the theoretical ideas of power politics of White governmentality by the French theorist Michel Foucault. The findings indicate that suppression of the Native Americans caused by the monopoly of the White hegemony is the crux of the whole fiasco that ultimately paved the way to silent the Native American narratives. It reveals that by reclaiming historical memory and using storytelling to establish their Indigenous identities, Native American authors dynamically fight against cultural erasure. These works serve as acts of cultural survival, presenting alternative epistemologies that contest colonial narratives and establish sovereignty over their own representation, in addition to exposing the mechanics of systematic oppression. Addressing historical injustices and dispelling persistent stereotypes are crucial goals of this study, which concentrated on the deliberate exclusion, misrepresentation, and ongoing stereotyping of Native Americans. This research is significant from the Native American perspective as it highlights the marginalized Native American narrative in its counter discursive approach and also highlights that how the privileged white sphere shapes, misinterprets, and discards an entire narrative based on falsified notions. This counter-discursive strategy fights misrepresentation by correcting misconceptions, promoting narrative sovereignty, and encouraging a more equitable portrayal of Native American experiences.